Exploring fluid-solid interfaces with Stefan Sokołowski - Borówko, M.; Ilnytskyi, J.; Pizio, O. (Condensed Matter Physics, 2016)
This special issue of "Condensed Matter Physics" is a collection of works prepared to mark the 65th birthday of Prof. Stefan Sokołowski, our good friend, co-worker and member of the Editorial Board of this journal. By presenting this issue we would like to add our contribution towards the celebration of his scientific achievements and valuable contributions to the science. The majority of the works in the issue deal with the description of fluid-solid interfaces by using modern statistical mechanics methods - the principal line of Stefan's research. However, some contributions from the related areas authored by his close friends are included as well.